Yield attributes and oil content of different mustard (Brassica campestris l.) varieties effected by different levels of fertilizers - Barman, Kamol Kumar; Mahmud, Sakil; Salim, Muhammad; Chowdhury, Bishan Lal Das (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> An experiment was conducted at the Agronomy Field Laboratory and Department of Biochemistry and Molecular Biology, Bangladesh Agricultural University, Mymensingh during the period from November 2013 to February 2014 to find out the appropriate fertilizer dose and best variety on the yield and oil content of mustard (Brassica spp). The experiment consisted of four fertilizer treatments viz., 0 fertilizer dose (control), 50% of recommended fertilizer dose, 100% recommended fertilizer dose and 150% of recommended fertilizer dose and three varieties viz. BINA Sarisha-5, BINA Sarisha-8 and Tori-7. The experiment was laid out in a two factor randomized complete block design with three replications. Both fertilizer dose and variety had significant effect on plant height (cm), number of branches plant-1, number of siliqua plant-1, siliqua length (cm), number of seeds siliqua-1, 1000 seed weight (g) and oil content (%). The interaction of fertilizer dose and variety had significant effect on all the plant characters except oil content of mustard (Brassica spp). The best result of the above characters was recorded in 100% recommended fertilizer dose in combination with BINA Sarisha-8. The next best result was obtained from 100% recommended fertilizer dose in combination with BINA Sarisha-5. Asian J. Med. Biol. Res. March 2016, 2(1): 143-147 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>